2021
DOI: 10.22270/ujpr.v6i2.561
|View full text |Cite
|
Sign up to set email alerts
|

The National Campaign for the Mass Treatment of Trachoma: Monitoring Coverage and Practices of Mass Drug Administration (Mda) in Yemen- Follow-Up Study

Abstract: Background:  Trachoma is a communicable infection of the eye by certain strains of the Chlamydia trachomatis. It is the principal cause of loss of sight globally. Mass drug administration (MDA) with azithromycin is a foundation stone of World Health Organization (WHO)’s global struggle to eradicate trachoma by 2020.  Aims: The main objectives of the campaign's third monitoring are to check improvement of interventions and improvement of quality across times and activities implemented in seven selected di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Respondents who had better knowledge about the azithromycin mass treatment were four times more likely to take azithromycin than those who had worse knowledge about AMT. This is agreed with the study conducted in four districts of the Amhara region, which indicated that having knowledge about the mass drug administration campaign makes people three times more likely to take AMT than their counterparts [ 20 ]), the study conducted in Awi zone, Amhara region which showed that provider message about AMT campaign increases the uptake of azithromycin and reduces fear of side effects [ 12 ], and effective social mobilization activities about the campaign is essential for successful program implementation [ 27 ]). Furthermore, this finding is consistent with the study conducted by Amarillo and his colleagues that health education and promotion activities, utilizing locally translated messages, education and communication materials, and other media, may increase the community’s level of awareness and knowledge on the campaign [ 28 ].…”
Section: Discussionsupporting
confidence: 57%
“…Respondents who had better knowledge about the azithromycin mass treatment were four times more likely to take azithromycin than those who had worse knowledge about AMT. This is agreed with the study conducted in four districts of the Amhara region, which indicated that having knowledge about the mass drug administration campaign makes people three times more likely to take AMT than their counterparts [ 20 ]), the study conducted in Awi zone, Amhara region which showed that provider message about AMT campaign increases the uptake of azithromycin and reduces fear of side effects [ 12 ], and effective social mobilization activities about the campaign is essential for successful program implementation [ 27 ]). Furthermore, this finding is consistent with the study conducted by Amarillo and his colleagues that health education and promotion activities, utilizing locally translated messages, education and communication materials, and other media, may increase the community’s level of awareness and knowledge on the campaign [ 28 ].…”
Section: Discussionsupporting
confidence: 57%